The English Pronunciation of Buginese Students in English Department of IAIN Palopo - Annisa, Nurul Cahyu; Wahibah, Wahibah (Faculty of Education and Teacher Training of IAIN Palopo, 2020)
This paper investigated the pronunciation especially about the labiodental fricative sound by Students with a Buginese background in the English Department at Tarbiyah Faculty and Teacher Training in 2019-2020. The purpose of this study was to determine the ability of students with Buginese backgrounds to produce labiodental fricative sounds in English. The method used in this research is descriptive qualitative method.The populations were Buginese students in English department at the Tarbiyah Faculty and Teacher Training at IAIN Palopo. To choose the samples, the writersused a purposive sampling technique, in which the researchers took 10 samples divided into several levels, namely 2 people from the second semester, 2 people from the fourth semester, 4 people from the sixth semester, and 2 people from the eighth semester. All samples are students with Buginese background. From a series of studies that have been carried out, the results obtained in this research are students with a Buginese background get some problems in English pronunciation, especially in labiodental fricative / f / and / v / sounds. Because the Buginese language does not have labiodental fricative sounds and there are transfer errors made by students when pronouncing English words.